PHYSICAL QUALITY ANALYSIS OF ‘ROTI MANIS’ AT BAROKAH BAKERY IN LAHAT - Ineke Kesuma Ningsih; Fitri Electrika D. Surawan; Zulman Efendi (BPFP Faperta UNIB, 2015)
The purpose of this research was to determine the percentage of each type of ‘roti manis’ physical damage, to identify factors causing the damages, and to determine whether the percentage amount of damage was whithin the business control limit. Types of damage observed were broken, too small in size, in appropriate form, over heated or burned. Observation was conducted during 16 working days (one month) at Barokah Bakery in Lahat. Result of the research showed that the broken damage was 1,31%; the too small in size was 1,1%; the unacceptable form was 0,98%; and no damage of over heat. Based on the causal effect analysis, it was found that the main factor causing ‘roti manis’s damages was caused by process inadequately. Result of diagram control analysis showed that the overall average damage was 3,4% with the upper limit was 5,2% and the lower limit was 1,6%. The percentage of the damage was considered high but it was within the company control limit of 2-4%